A multi-club analysis of the locomotor training characteristics of elite female soccer players. Issue 5 (1st December 2022) - Myhill, Naomi; Weaving, Dan; Barrett, Steve; King, Ryan; Emmonds, Stacey
ABSTRACT: Objective: Quantifying differences in locomotor characteristics of training between two competition levels and between training days within elite female soccer players. Methods: Foot-mounted inertial measurement unit (Playermaker) data were collected from 293 players from three Women's Super League (WSL; n = 76) and eight Women's Championship (WC; n = 217) teams over a 28-week period. Data were analysed using partial least squares correlation analysis to identify relative variable importance and linear mixed effects models to identify magnitude of effects. Results: WSL players performed more high-speed running distance (HSR; >5.29 m∙s −1 ), sprint distance (SpD; >6.26 m∙s −1 ), acceleration (ACC; >3 m∙s −2 ) and deceleration (DEC; <-3 m∙s −2 ) distance than WC players. The largest difference between WSL and WC in HSR and HSR per minute occurred on MD-4, (354.7 vs . 190.29 m and 2.8 vs . 1.7 m∙min −1 ). On MD-2, WSL players also covered greater SpD (44.66 vs . 12.42 m), SpD per minute (0.38 vs . 0.11 m∙min −1 ) and HSR per minute (1.67 vs . 0.93 m∙min −1 ). Between training days both WSL and WC teams reduced HSR and SpD but not ACC and DEC distance from MD-4 to MD-2, with MD-4 the highest training day of the week. Conclusion: MD-4 is a key training day discriminating between competitive level. HSR and SpD volume and intensity is tapered in WSL and WC players, however there is less clear taper of ACC or DEC. As such, WC teams could increase the volume and intensity of HSR on MD-4 to mimic locomotor activities of those at a higher standard.